Opaque algorithms and differential privacy: can there be transparency without compromising protection? (Forseti. Law Review, 2025)
This article analyzes the tension between algorithmic transparency and differential privacy in the context of increasing implementation of Artificial Intelligence systems in sensitive areas. Through an interdisciplinary analysis that integrates legal, technological, and ethical perspectives, it examines how opaque algorithms compromise accountability and how differential privacy, while protecting personal data, can undermine algorithmic accuracy.
Keywords: Opaque algorithms; Differential privacy; Algorithmic transparency; Data protection